Trend Analysis of Rainfall and the Standardised Precipitation Index (SPI) in Johor - ABDULLAH SANI, NUR SHAFURA AINI; RAHMAT, SITI NAZAHIYAH (Recent Trends in Civil Engineering and Built Environment, 2022)
Johor has experienced a number of flood events including a recent severe flood. The objectives of this study are to analyse the trend analysis of rainfall at the selected stations in Johor area and to investigate the annual trend of dry and wet events in Johor. The rainfall data was collected from eight (8) rainfall station in Johor with period of 1980 to 2017 and was obtained from the Department of Irrigation and Drainage (DID), Malaysia. Mann-Kendall test is the non-parametric test had been used in this study to analyse the trend analysis of rainfall and Standardised Precipitation index (SPI) was applied to classify the dry and wet events. Temporal trend in the rate of occurrence of dry and wet events (inter-arrival times) were also examined. The results shows that five (5) stations namely Ladang Paya Lang in Segamat, Ladang Sungai Tiram in Johor Bahru, Stor JPS Batu Tiga in Mersing, Ladang Permatang in Kota Tinggi and Stor JPS in Endau stations often having dry events and less wet events. It was observed that most of the stations showed decreasing trend in rainfall analysis by using Mann-Kendall test and downward trend in SPI analysis. The benefits of investigating the annual trend of dry and wet events is for early detection of climatic impact such as drought and flood and community can be prepared and be able to adapt the drought and flood events in the future.